Islamic Republic of Afghanistan : Staff Report for the 2019 Article IV Consultation and the Sixth Review under the Extended Credit Facility Arrangement-Press Release; Staff Report; and Statement by the Executive Director for Islamic Republic of Afghanistan. (IMF Staff Country Reports; Country Report, 2019)
This paper presents 2019 Article IV Consultation with Republic of Afghanistan and its Sixth Review Under the Extended Credit Facility Arrangement. Despite difficult circumstances, the Afghan authorities have continued to demonstrate strong commitment to the economic program supported by the Extended Credit Facility arrangement. Given the uncertain outlook dominated by downside risks, policies should focus on maintaining macroeconomic and financial stability and putting the conditions in place for stronger and more inclusive growth, led by the private sector. The authorities have made progress with their self-reliance agenda, yet strong financial support from donors is needed to help Afghanistan stay on the path to greater prosperity. Fiscal policy should continue to target a broadly balanced budget, supported by fair and sustainable domestic revenue mobilization and strong financial support by donors. Resources should shift toward pro-growth and pro-poor outlays and create fiscal space to meet the country's considerable development needs.